Tracce Significanti. Arte Italiana oggi : Art Athina 6'98 - Bonito Oliva, Achille; Dimakopoulou, Giulia; Fanelli, Franco; Koskina, Katerina (Athens : Hellenic Art Galleries Association, 1998)
Anselmo, Giovanni ; Arienti, Stefano ; Benetti, Mauro ; Botto & Bruno ; Cucchi, Enzo ; Cuoghi & Corsello ; Fermariello, Sergio ; Ferrara, Aldo ; Fraterno, Matteo ; Kaufmann, Massimo ; Levini, Felice ; Mazzei, Vedova ; Monti, Paolo ; Moro, Liliana ; Nunzio ; Parenti, Alessia ; Pessoli, Alessandro ; Pirri, Alfredo ; Renzogallo ; Romano, Alfredo ; Sabato, Sabrina ; Sassella, Ivano ; Stoisa, Luigi ; Zevola, Giuseppe
biografie
Engels & Italiaans & Engels
Tracce Significanti. Arte Italiana oggi, Comune di Atene - Gazi, Novembre 1998
boek
Keywords: Italië